Revolutionizing Aquaculture Strategy: The Journey of eFishery from Startup to Unicorn with Non-App-Based Technology - Dian Alanudin; Muhammad Miqdad Robbani (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
The emergence of the fishery, founded by Gibran, has revolutionized the aquaculture landscape through its innovative technology-driven solutions. Beginning with the development of an automated fish-feeding device in 2012, eFishery's journey from startup to unicorn status has been marked by transformative advancements in fish farming practices. This abstract explores eFishery's trajectory, encompassing its strategic evolution, technological innovations, and significant milestones. From securing series D financing in 2023 to pioneering non-app-based technology, the fishery has reshaped the aquaculture industry, empowering fish farmers worldwide with efficient, cost-effective solutions. Moreover, eFishery's expansion into shrimp farming technology and the launch of eFarm and eFisheryFresh demonstrate the company's commitment to continual product innovation. Through a blend of trial and error, technological prowess, and strategic foresight, fishery has cemented its position as a leader in aquaculture technology, driving sustainable growth and profitability in the sector.